Peran Public Relations Radio Cakra Bandung dalam Meningkatkan Loyalitas Pendengar di Masa Pandemi - R. Regina Dewanti; Intan Primasari (Journal on Education, 2023)
The increasing number of other radio stations that continue to grow rapidly and continue to compete to provide high quality programs. Radio Cakra Bandung is one of the private radio stations in the city of Bandung, the arrival of Covid-19 in Indonesia in March 2020, Radio Cakra began to feel the impact, namely the instability of the number of listeners. In addition, Radio Cakra Bandung must be able to retain old listeners and reach new listeners to survive in the broadcasting industry which is experiencing a decline in listeners. Since the covid-19 pandemic Radio Cakra Bandung has innovated through digital form in forming PR activities in order to gain loyalty from listeners so that they are able to compete and survive during the Covid-19 pandemic. The purpose of this study was to determine the role of public relations in increasing the loyalty of Radio Cakra Bandung listeners during the Covid-19 pandemic. The theory used in this study is the theory of Rusadi Raslan (2016) about the four roles of public relations. The method used is descriptive qualitative research method. As well as data collection techniques and data analysis techniques carried out by conducting in-depth interviews, observation, and documentation. The results show that of the four roles of PR practitioner Rosady Ruslan (2016), there is one role that has not been carried out by PR Radio Cakra Bandung, namely communication technician. However, other roles such as expert advisor, communication facilitator, and problem solving facilitator have been carried out well.